The therapeutic effects and antioxidant properties of epigallocatechin-3 gallate: A new review - Beyaz, Seda; Gok, Ozlem; Aslan, Abdullah (Pamukkale University, 2022)
The aim of this review is to investigate the possible protective and preventive effects of epigallocatechin-3 gallate (EGCG) in terms of human health including hepatoprotective, neuroprotective, cardioprotective, nephrotoxicity and anticancer effects. Green tea is one of the most consumed beverages in many countries, especially in Turkey and it plays protective roles in the treatment of various diseases via the polyphenol it contains. It is known that EGCG, which is the main bioactive polyphenol in green tea, has versatile bioactivities. It has been determined that EGCG has the highest free radical scavenging ability among common phenolic compounds. It regulates gene expression and molecular signaling pathways by inhibiting oxidative stress and inflammation. In addition, it prevents cell death by suppressing cytokine production and neutrophil migration in inflammatory diseases. With the studies conducted in the last decade, it has been determined that EGCG has anticancer, antioxidative, antiinflammatory, antidiabetic, antitumor, antihypertensive and neuroprotective activities. Especially, its anticancer effect has been found to have chemopreventive and chemotherapeutic activities in various cancer types such as colon, lung and breast cancer with in vivo and in vitro studies conducted to investigate molecular targets. This review was written to examine the possible protective and preventive effects of EGCG in terms of human health, including its hepatoprotective, neuroprotective, cardioprotective, nephrotoxicity and anticancer effects. © IJSM 2022.
Keywords: Anticancer; Antioxidant; Epigallocatechin-3-gallate; Green tea; Polyphenol